2023
DOI: 10.1021/acsami.2c20504
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-like Hierarchical Framework Nucleic Acid for Real-Time Imaging of Intracellular Trafficking

Abstract: Framework nucleic acids (FNAs) represent a new type of DNA-based nanomaterials and possess great potentials in biosensing, bioimaging, and molecular delivery. Hierarchical DNA nanostructures that consist of multiple FNA monomers increase the capacity for drug delivery and multifunctional modification. However, there are relatively few studies devoted to the behavior and regulation of hierarchical FNAs in living cells, impeding their further applications. Herein, we constructed a dendritic nanostructure with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Using single-particle tracking, Liang et al [150] demonstrated that TDNs rely on cave proteins for rapid internalization. Hu et al constructed a dendritic layered DNA structure by the self-assembly of five identical TDNs [151] . The nucleic acid dendrimer framework showed good intracellular delivery, high biocompatibility, and stability in the cellular environment.…”
Section: Delivery Unitmentioning
confidence: 99%
“…Using single-particle tracking, Liang et al [150] demonstrated that TDNs rely on cave proteins for rapid internalization. Hu et al constructed a dendritic layered DNA structure by the self-assembly of five identical TDNs [151] . The nucleic acid dendrimer framework showed good intracellular delivery, high biocompatibility, and stability in the cellular environment.…”
Section: Delivery Unitmentioning
confidence: 99%
“…13 Cell internalization was a crucial prerequisite for asPNA to exert a role in gene regulation. Although the tetrahedral FNA monomers and G 1 dendrimers (the overhangs of monomers at the vertex) were reported to enter cells without the assistance of transfection reagents, 17,18 the potential of G 2 as a novel drug delivery material remained unexplored. Hence, the cell uptake efficiency of asPNA was investigated.…”
mentioning
confidence: 99%